A case report of a very late response to 5-azacytidine in a patient with lower risk myelodysplastic syndrome: Time to update treatment guidelines for lower risk patients. Issue 17 (April 2018) - Spetsieris, Nikolaos; Diamantopoulos, Panagiotis; Zervakis, Konstantinos; Giannakopoulou, Nefeli; Rougala, Niki; Garefalakis, Georgios; Skarlatou, Vasiliki; Viniou, Nora-Athina
Abstract: Rationale: The hypomethylating agent 5-azacytidine has been approved in Europe for patients with intermediate 2 and high (i.e., higher) risk myelodysplastic syndrome according to the International Prognostic Scoring System (IPSS). A total of 91% of all first responses in higher risk patients occur within 6 cycles of treatment; however, data regarding the time to first response in clinical trials with lower risk patients are not available. Patient concerns: Our case describes the late response of a lower risk (intermediate 1 according to the IPSS and intermediate according to the IPSS-R) patient to 5-azacytidine treatment. Diagnosis and interventions : Once diagnosed, the patient started supportive treatment due to persistent pancytopenia and recurrent infections. The use of a hypomethylating agent was decided because the patient was transfusion dependent, and suffering from recurrent severe febrile infections due to neutropenia. Other possible causes of fever except infections in the context of his neutropenia were excluded. Outcomes : After the 12th cycle of 5-azacytidine the patient showed a hematologic response, with transfusion independency and with no recurrent febrile episodes. Lessons: This case report probably indicates that a subset of patients who belong to the lower risk category according to the previous prognostic systems and to the intermediate one according to the IPSS-R, may benefit from prolonged treatment with the drug. The indication of 5-azacytidine in Europe for patients with higher risk myelodysplastic syndrome (MDS) (according to the IPSS) could possibly include a wider range of patients if updated according to the IPSS-R.